Lactobacillus rhamnosus and Lactobacillus casei Affect Various Stages of Gardnerella Species Biofilm Formation - He, Yuanhui; Na, Risu; Niu, Xiaoxi; Xiao, Bingbing; Yang, Huixia (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial vaginosis (BV) and its recurrence are most commonly associated with the formation of Gardnerella species biofilm. Probiotics are typically used to treat BV; however, the optimal period of Lactobacillus probiotic application in BV treatment remains uncertain. The present study aimed to explore the effects of Lactobacillus rhamnosus and Lactobacillus casei on various stages of biofilm formation in Gardnerella species. The biofilm-forming ability of seven strains, including one Gardnerella vaginalis ATCC 14018 and six clinically isolated Gardnerella species, was determined via gentian violet staining assay. Moreover, the sensitivity of the planktonic and biofilm forms toward metronidazole and clindamycin was assessed via microdilution broth method. L. rhamnosus Xbb-LR-1 and L. casei Xbb-LC-1 were added during various stages of biofilm formation in Gardnerella species and were cocultured for 24 h. The biofilm thickness of each sample was determined via confocal laser scanning microscopy (CLSM). The relative quantity of Gardnerella species/Lactobacillus in each sample was obtained via real time polymerase chain reaction method, and the pH value was obtained using a pH indicator paper. Biofilm formation by Gardnerella species in a medium with distinct pH values was observed via gentian violet staining, CLSM, and scanning electron microscopy (SEM). The biofilm increased the resistance of Gardnerella species toward metronidazole and clindamycin. L. rhamnosus added at the initial biofilm formation stage in Gardnerella species exhibited highest inhibitory effect, with a percentage inhibition of 38.17% ± 1.35%. When the pH value of the culture medium was <4.5 or >6.5, ATCC 14018 could hardly form a biofilm; however, at pH ≥4.5 and ≤6.5, it was able to form a stronger biofilm. The amount of biofilm attained maximum value at optical density of 3.29 ± 0.28 (595 nm), pH 5.5, and at 36 h. Biofilm formation increases the resistance of Gardnerella species toward antibiotics. Maintaining an acidic vaginal environment with pH <4.5 and a vaginal microbiota dominated by Lactobacillus remarkably prevents the formation of Gardnerella species biofilm at the initial stage, which further has a significant impact on the treatment and prevention of biofilm-related infections.